Intelligent-Based Systems Engineering - Tolk, Andreas; Jain, Lakhmi C. (Intelligent Systems Reference Library,, 2011)
The International Council on Systems Engineering (INCOSE) defines Systems Engineering as an interdisciplinary approach and means to enable the realization of successful systems.   Researchers are using intelligence-based techniques to support the practices of systems engineering in an innovative way. This research volume includes a selection of contributions by subject experts to design better systems.